2019
DOI: 10.1038/s41598-019-47164-x
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between pubertal timing and markers of vascular and cardiac structure and function in men and women aged 60–64 years

Abstract: Earlier age at menarche has been associated with higher risk of coronary heart disease, but the mechanisms underlying the association remain unclear. We assessed the relationship of pubertal timing, in both men (n = 672) and women (n = 713), with vascular (carotid intima-media thickness (cIMT), pulse wave velocity (PWV)) and cardiac (left ventricular (LV) structure and function) measures recorded at age 60–64 yrs in a British birth cohort study. Regression models found that earlier menarche was associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 43 publications
1
25
1
1
Order By: Relevance
“…In line with previous observational evidence [31,32,[66][67][68][69][70][71][72][73], our results show that AAM is inversely associated with BMI, fat mass, and fat percentage in middle-age. The inverse relationship between AAM and BMI in adulthood was also recently supported by Mendelian randomisation studies [48,74,75].…”
Section: Aam and Midlife Characteristicssupporting
confidence: 93%
“…In line with previous observational evidence [31,32,[66][67][68][69][70][71][72][73], our results show that AAM is inversely associated with BMI, fat mass, and fat percentage in middle-age. The inverse relationship between AAM and BMI in adulthood was also recently supported by Mendelian randomisation studies [48,74,75].…”
Section: Aam and Midlife Characteristicssupporting
confidence: 93%
“…However, if we had this variable and adjusted in the analysis of the association between age at menarche and metabolic cardiovascular risk factors, the effect mediated by adult body composition would be reduced, hiding an important explanatory factor of the association. Therefore, the absence of the information on pre-pubertal body composition did not bias the analyzes performed in this study, since adult body composition accounted for most of the relationship between age at menarche and metabolic cardiovascular risk factors 23 . Despite the fact that measures of body composition and metabolic cardiovascular risk factors were evaluated at the same time, which could cause doubts as to the validity of the associations, violating the principle of temporality, we do not believe that this could have occurred in this study.…”
Section: Discussionmentioning
confidence: 99%
“…We also observed no association when SITAR variables were used to represent pubertal timing. Previous analysis in NSHD found no association between age at menarche and all-cause mortality suggesting that different mortality rates by pubertal timing in women are unlikely to have biased this finding 49 . In sensitivity analyses we found that that the associations between older age at menarche and higher AgeAccel attenuated following adjustment for cell composition.…”
Section: Our Finding Of An Association Between Faster Linear Growth Imentioning
confidence: 72%